High performance Ni3S2/Ni film with three dimensional porous architecture as binder-free anode for lithium ion batteries. (1st September 2016) - Zhang, Zijia; Zhao, Hailei; Xia, Qing; Allen, Jason; Zeng, Zhipeng; Gao, Chunhui; Li, Zhaolin; Du, Xuefei; Świerczek, Konrad
Graphical abstract: Highlights: Direct growth of Ni3 S2 nanoplates on Ni foam is used as binder-free anode. The Ni3 S2 /Ni electrode presents nest-like highly porous architecture. High specific capacity and excellent rate-capability are achieved. Abstract: A facile one-step method is developed for the direct growth of Ni3 S2 nanoplates on a conductive nickel foam, which interwove together to form nest-like highly porous microstructure. When used as a binder- and conductive-agent-free electrode, the Ni3 S2 /Ni electrode demonstrates remarkable electrochemical performance with a superior cycling stability and a high rate capability, proving its potential applicability as a high performance anode for lithium ion batteries. The excellent electrochemical properties can be attributed to the 3-dimesional (3-D) structure of the Ni foam uniformly covered with a porous layer of Ni3 S2 nanoplates. This structure provides excellent electrical contact between the active material and the current collector, a large electroactive surface area as well as well-sustained electrode integrity. The Ni3 S2 /Ni electrode maintains a reversible capacity of 623 mAh g −1 after 150 cycles at a current density of 0.1 A g −1, and delivers a high reversible capacity of 377 mAh g −1 at a high current density of 1.5 A g −1 . The observed surplus capacity is found to originate from an interface storage process via a pseudocapacity-like storage mechanism.